Ploidy level of the cultivated yams (Dioscorea cayenensis/D. rotundata complex) from Benin Republic as determined by chromosome counting and flow cytometry - Dansi, A.; Pillay, M.; Mignouna, H.; Daïnou, O.; Mondeil, F.; Moutairou, K. (2000)
The ploidy level of ninety Guinea yam (Dioscorea Cayenesis/D. rotundata complex) cultivars identified within Benin were determined by both chromosome counting from root tip cells and flow cytometry. Three different ploidy levels (4x,6x,8x,) were detected among the samples. Eighty cultivars were tetraploid, five were hexaploid, three were octoploidy and two 4x and 8x ploidy levels. Chromosome counts were in agreement with data from flow cytometry that provides an easier assay for ploidy analysis. Flow cytometry was found to be a reliable tool for rapid determination of ploidy level in yam.